Membangun Kesadaran Investasi Syariah pada Generasi “Z” dengan Penerapan Model Edukasi Pasar Modal - Dito Rinaldo; vina Anggilia Puspita (Universitas Ekuitas Indonesia, 2025)
The low literacy level of the sharia capital market in Indonesian society emphasises the significance of early education initiatives. Previous research found that more than half of the Java students surveyed were not actively engaging in the stock market. Based on the actual occurrence, the goal of this community service program (PKM) is to educate SMK Baabul Kamil Jatinangor students about the Sharia capital market. The PKM programme will use 5 capital market education model materials for stages 1 and 2, namely: lifestyle education, financial planning education, education on the halal idea of sharia capital markets, basic capital market concepts, and a comparison between sharia and conventional capital markets. This PKM program was successful in boosting students' capital market literacy from an average score of 1.125 (very low) to 2.945 (low ). Because the PKM program only applies stage